Challenges of budgetary control system and its impact in management performance in local government authorities in Tanzania: Case study of Kisarawe district council (KDC) - Kilangaly, Alex. N (Mzumbe University, 2024)
A Dissertation Submitted to Mzumbe University, Dar es Salaam Campus College in Partial Fulfillment of the Requirements for the Award of Master Degree in Accounting and Finance (MSc-A&F)